A Numerical Study on Magnetic Fields Effects on Stem Cell Differentiation - Miskon, Azizi; Uslama, Jatendra (International Journal of Integrated Engineering, 2010)
The objective of this paper is to provide the fundamental mathematical formula to predict the effect of magnetic fields (MF) on stem cell differentiation. The data were reviewed from journals related to the effects of magnetic fields on stem cell differentiation. These data were given a value for differentiation which is related to their MF strength with these conditions; MF strength that does not affect the stem cell differentiation given the value of zero, MF strength that results in stem cells death given the value of 1, and the MF strength that affects stem cells The differentiation given the value between 0.1 and 0.9. graph was plotted according to these data and the mathematical equation is designed from the graph. From this review, we suggest that the intensity of MF that can affect the stem cell differentiation is between 600μT and 9.4T in which the cell differentiation will not occur with intensity of less than 10μT and intensity of more than 12T will cause the death of stem cells. We also suggest that the limit of MF effects on stem cell differentiation lies between 10 μT and 600 μT, and the limit of MF strength that can lead to the death of stem cells lies between 9.4 T and 12 T. It can be concluded that the exposure of MF on stem cell differentiation depends not only on the MF intensity, but also on the period of exposure.